Green Skill Training:Meningkatkan Ketrampilan Warga Mengelola Manajemen Bank Sampah - Masine Slahanti; Nisa Novia Avien Christy; Enggar Dhian Pratamanti; Soegihartono Soegihartono (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
The problem of waste is one of the problems that has become a concern for various parties, it cannot be denied that every day there must be waste that must be disposed of, both from industry and from households in the form of solid or liquid waste plastic or in the form of other waste. Discussion of waste processing has been around for years, in line with the increasingly developing industry and increasingly dense housing. Population growth accompanied by the high flow of urbanization to cities as a result of modernization, has led to an increasing volume of waste that must be managed every day Purwodinatan sub-district is part of the sub-districts that participate in the management of waste banks, however, it is felt that waste banks still need to be given an understanding of improving management maximally within the management system. On this occasion, activities for the community focused on providing insight and knowledge of waste bank management with Green Skill Training management that regulates administration with the aim of administratively managing waste banks better. The activity was carried out by providing material in a seminar forum attended by waste bank managers from the RW001 management consisting of five RTs, each represented by three people: the Chairperson, Treasurer, and Secretary. This community service activity can increase insight and knowledge not only for waste bank managers but also encourage community participation in waste bank activities.